Teachers' and Students' Feedback on Sociocultural Interactive Digital Modules for Science Literacy and Problem-Solving: A Transformative Learning Approach - Merta Simbolon; Jesi Jecsen Pongkendek; Anderias Henukh; Diana Rochintaniawati (Journal Evaluation in Education (JEE), 2025)
Purpose of the study: This article examines the practicality of sociocultural-based interactive digital modules in improving students' science literacy and problem-solving skills by integrating a transformative learning approach. Methodology: This descriptive research analyzes students' and teachers' responses to the developed interactive digital module. The study was conducted in junior high schools in Merauke Regency and Boven Digoel Regency, South Papua Province, totaling six schools. Data were collected through responses from 6 science teachers and 60 students involved in learning science with the module. Main Findings: The results showed that this module is efficient for use in science learning, according to the responses from teachers and students. Feedback from teachers and students indicated that this module is efficient to use in science learning, as seen from the average total percentage given by teachers of 95% in the efficient category and provided by students of 95.53% in the efficient category. Through this article, the developed interactive digital module is feasible to use in science learning to improve science literacy and problem solving skills of junior high school students.. Novelty/Originality of this study: The module is designed with an approach that combines Papuan local wisdom values and transformative learning principles. This approach is rarely implemented simultaneously in the context of science learning to improve students' understanding of science. In addition, the interactive digital module not only focuses on understanding science materials but also connects them with local wisdom to increase the relevance of learning to students' daily lives.